From melancholic to happy immigrant: Staging simpleton in the comedies of migration. (1st November 2019) - Meerzon, Yana
AbstractThis article examines devices of comedy, laughter and dramatic humour as technologies of ethics when it comes to staging migration in contemporary theatre. Looking at a tragic farce Hunting Cockroaches (1985), written by the Polish theatre artist Janusz Głowacki during his American exile, and a domestic melodrama Kim's Convenience (2012), written by a Korean Canadian Ins Choi, this article examines comedy as a particular dramatic model that can challenge staging migrants as agentless and voiceless victims. It asks, what happens when theatre artists begin to use stereotype to stage the trauma of displacement? To what extent is comedy truly capable of rendering the complexity of migration? And how ethical can the comedic representation of a migrant be?